2009
DOI: 10.21608/jacb.2009.93107
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATION OF GENETIC PARAMETERS FOR YIELD AND YIELD COMPONENTS AND SOME AGRONOMIC CHARACTERS IN TWO CROSSES OF BREAD WHEAT (Tritium aestivum L.)

Abstract: Three cultivars of bread wheat; Sakha 69, Sakha 93 and Sakha 94 were crossed in all six generations. P1, P2, F1, F2, BC1 and BC2 were obtained for two crosses;(Sakha 69 × Sakha 93) and (Sakha 93 × Sakha 94) to determine genetic parameters for number of days to heading and maturity, plant height, number of spikes per plant, number of kernels per spike, 100-kernel weight and grain yield per plant. The experiment was conducted at Sakha Agricultural Research Station during the growing seasons 2005/06, 2006/07 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
8
2
0
Order By: Relevance
“…Meanwhile, non of A, B or C scaling tests were significant, indicating the adequacy of the three parameter model to explain the type of gene action. These results are in general agreement with those of Tammam (2005), El-Hag (2006), Abd El-Rahaman, Magda and Hammad (2009), Aboshosha and Hammad (2009), Type of gene action Cross 2 = Line 1 × Sakha 94 Cross 3 = Sakha × Gemmiza 9…”
Section: Scaling Test and Generation Mean Analysissupporting
confidence: 90%
“…Meanwhile, non of A, B or C scaling tests were significant, indicating the adequacy of the three parameter model to explain the type of gene action. These results are in general agreement with those of Tammam (2005), El-Hag (2006), Abd El-Rahaman, Magda and Hammad (2009), Aboshosha and Hammad (2009), Type of gene action Cross 2 = Line 1 × Sakha 94 Cross 3 = Sakha × Gemmiza 9…”
Section: Scaling Test and Generation Mean Analysissupporting
confidence: 90%
“…The results indicated that the parental varieties differed in their performance for all traits. These results are in agreement with those obtained by El-Hawary (2006); Aboshosha and Hammad (2009); Gebrel (2010) and Abd El-Lateef (2012).…”
Section: Mean Performancesupporting
confidence: 93%
“…The cross P 1 x P 2 was the best in the two seasons for spikes number/plant and grains number/spike. These results are in harmony with those of Shehab El-Deen (2008); Aboshosha and Hammad (2009); Gebrel (2010); Sulaiman (2011); Abd El-Lateef (2012) and . indicated the presence of true differences among these genotypes.…”
Section: Mean Performancesupporting
confidence: 87%
See 1 more Smart Citation
“…In general, most of authors obtained variable estimates of heritability in narrow and broad senses although their values were close to each others because of the smaller values obtained for the dominance. In this respect, Aboshosha and Hammad (2009) indicated that the calculated quantities A, B and C of the scaling test revealed the importance of additive effect which was larger and greater than dominance effect for 100-kernel weight; grain yield/plant and plant height. Therefore, the objective of this study was directed to investigate the effect of normal and late sowing dates, on the performances of three hybrids resulted from crossing different cultivars and lines with respect to their earliness characteristics.…”
Section: Introductionmentioning
confidence: 93%